DEVELOPMENT OF SOLAR HEAT CONCENTRATION BOX DRYER AND LM 35 SENSOR AS TEMPERATURE MEASURING DEVICE - Umukoro, Edafewhuotu; Alebu, O.; Okocha, G.O; Esekhaigbe, I. F. (International Journal of Engineering Technologies and Management Research, 2022)
The solar heat concentration box is a system which convert the solar energy to heat energy in a closed system for farmers to dry their farm produce. The system uses solar collector to harness energy from the Sun and concentrate it on a drying chamber to remove moisture from plantain, tomatoes, yam and pepper harvested from the farm. The system have three compartments system. Firstly, heat chamber. The heat chamber is made up of a solar glass collector, reflector foil and a rectangular wooden box. This chamber converts the Sun energy to heat energy. It is mounted at angle of 60o to the drying chamber. Secondly, the drying chamber. The drying chamber comprises of a cuboids, tray and isolating material. This is the chamber where the farm produce is laid and removal of moisture takes place. Thirdly, an electronic system which is made up of LM 35 sensor is used to convert the heat distribution inside the drying chamber to temperature. The LM 35 is interface with an Ardiuno UNO microcontroller. The microcontroller converts the analog signal output generated from the sensor to a digital output signal which is been display on visual system. The electronic device will enable farmers measure the temperature of the drying chamber at a particular time or period of the day. The system will enable farmers to dry perishable farm produce which is seasonal. This will reduce food shortage and increase in the cost of such seasonal and perishable farm produce during harvest and off-season.